THE EFFECT OF DIETARY PORTION CUT ON THE BODY FAT OF ADULTS - FIJI ANTONY; Sharma, Anuka (Innovare Journal of Food Sciences, 2019)
Objective- The study was planned to determine the effect of dietary portion cut on the body fat of individuals with passage of time Methods- Total 323 adults with general good health underwent dietary intervention to decrease the portion size of the diet they were taking to reduce calorie intake to 1200kcal/day. In order to determine the effect of treatment, a new variable i.e. rate of change of various dependent variables (BMI, body fat percent & muscle mass percentage) were determined for each individual. A multiple linear regression model was run to determine the effect of independent variables (age, gender, initial measurement of dependent variables) on the rate of change of dependent variables. Results- The mean rate of change of BMI was hardly influenced by age, gender or initial BMI. The rate of change of body fat percent was hardly influenced by age as indicated by a low coefficient close to zero, although statistically significant (p=0.0236).The coefficient for female indicated that the mean rate of change of body fat percent in females was higher(-0.0532) as compared to males (-0.021) keeping other variables fixed, and the effect was statistically significant (p=0.0028).The initial body fat percent had also significant effect on the rate of change of body fat percent (p=< 0.0001).The initial muscle mass percent had significant effect on the rate of change of muscle mass percent of individuals (p=0.0032). Conclusion- The dietary intervention of portion cut to decrease calorie intake results in significant decrease in body fat percent in females in comparison to males.